Dental Neglect Score and its Association with Oral Hygiene and Dental Caries among Adults visiting A Tertiary Hospital in Kathmandu - Bhattarai, Rosina; Khanal, Sunita; Shrestha, Sujita; Rao, G. Nagaraja (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Dental neglect is a harmful behavior which brings many unwanted consequences in oral health. It has been found to be related to poor oral hygiene and increase in oral diseases. Dental neglect scale is a valid measure to record dental neglect among adults. Objective: To assess dental negligence using Dental Neglect Scale (DNS) questionnaire and assess its association with oral hygiene status and dental caries. Methods: Study consisted of convenient sample of 287 adults visiting Kantipur Dental Hospital who were given six-item Dental Neglect Scale questionnaire followed by oral examination using Oral Hygiene Index-Simplified (OHI-S) and Decayed Missing Filled Teeth (DMFT) index. Results: The mean DNS score was found to be 18.40. Statistically significant difference was seen between age of the participants and mean DNS score (P value 0.033) as well as with gender and mean DNS score (P value 0.001). Association between dental neglect score and DMFT categorised and OHI-S shows statistically significant difference the groups with p value 0.022 and 0.001 respectively. Conclusion: Dental neglect was found to be high among adults in Kathmandu and caries and oral hygiene status were significantly associated with dental neglect. Variation in dental neglect exists in relation to various sociodemographic variables like age and gender.